Struma Ovarii- Association with Pseudo-Meigs Syndrome and Raised S. CA-125: A Case Report - Parvin, Suraiya (Bangladesh Armed Forces Medical Journal, 2024)
The monodermal mature teratoma known as Struma Ovarii is a rare and uncommon form of ovarian tumours. It is primarily composed of thyroid tissue and is associated with hyperthyroidism, increased levels of S. CA-125 (Cancer Antigen-125), and pseudo-Meigs syndrome. Because the symptoms of this tumour are nonspecific, other extremely frequent ovarian lesions may be misdiagnosed and ignored. The majority of the time, incidental imaging and symptoms are used to make the first diagnosis of the cancer; histopathology is used to confirm the diagnosis. A good prognosis and successful curative treatment can result from surgically removing the tumour. The tumour's rarity makes misdiagnosis frequent. Nonetheless, a total abdominal hysterectomy combined with a bilateral salpingo-oophorectomy may be indicated in premenopausal patients in order to eradicate all symptoms. Ascites, hyperthyroidism, high S. CA-125 levels, and hydrothorax are all rare outcomes of struma ovarii. In this uncommon syndrome with negative cytology, individuals with ascites and pleural effusion should be examined for a differential diagnosis. Bangladesh Armed Forces Med J Vol 57 No (1) June 2024, pp 50-55